THE FUTURE OF WORK : TOLERANSI RISIKO, KEADILAN ORGANISASI, DAN KEBEBASAN DALAM BEKERJA TERHADAP MINAT BEKERJA MAHASISWA UNIVERSITAS SARJANAWIYATA TAMANSISWA - Auliya Rosiana; Eko Yulianto (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2023)
Technological sophistication is the essential thing needed to develop all aspects of industrial revolution 4.0. It emphasizes expanding job prospects and maximizing responsibility for completing work with a different approach. This revolution is related to the young millennial generation and Z generation in choosing the field of work. This generation prioritizes flexibility and simplicity and works effectively and efficiently. Different from the previous generation, they expected that everything should be organized with various bureaucratic and administrative policies. Currently, Z generation is primarily students in Higher Education. The actual situation shows that most students have no plans to decide the type of work they want to. They doubt about their passion and potential. Therefore, this study aimed to map the students work plans so that supervisors can direct their interest in concentration according to their potential. This study identified and proved the suitable work system for Z generation. In addition, this research aimed to find out whether risk tolerance, justice, and freedom at work affect the student’s interest in working in the future. The population was students of the Management Program, Faculty of Economics, Universitas Sarjanawiyata Tamansiswa. The method used multiple regression analysis methods to test the relationship pattern that has a theoretical basis. The result of this study showed that risk tolerance and justice positively affect the interest to work in the future. Nevertheless, freedom of work does not affect interest to work in the future.